Pengaruh Perceived Organizational Support terhadap Work Engagement pada Barista Starbucks di Kota Bandung - Razka Razkiandra; Sita Rositawati (UNISBA Press, 2024)
Abstract. The organization requires employees with high levels of energy in their work, dedication to their tasks, and enthusiasm that immerses them in their job activities (Bakker & Leiter, 2010). This is reflected in employees who have work engagement. According to Schaufeli et al. (2002), work engagement refers to a positive affective-motivational state characterized by vigor, dedication, and absorption. Work engagement occurs when there are high job demands and job resources. Perceived organizational support is one of the job resources that encompasses three dimensions: fairness, supervisor support, and organizational rewards and job conditions. The objective of this study is to examine the extent of the influence of perceived organizational support and its dimensions on work engagement among 100 Starbucks baristas in Bandung. The measurement tools used in this study are the Utrecht Work Engagement Scale-17 (UWES-17) developed by Schaufeli et al. (2002) and the Survey of Perceived Organizational Support (SPOS) by Eisenberger et al. (1986), adapted by Avianti & Hatta (2022). The results indicate a significant influence of perceived organizational support on work engagement at 28.5% (R Square = .285). The dimensions of organizational rewards and job conditions have a significant impact of 20.8%. On the other hand, the fairness dimension has the lowest impact at 1.8%. Abstrak. Organisasi membutuhkan karyawan yang mempunyai tingkat energi yang tinggi dalam bekerja, berdedikasi dengan pekerjaannya, dan antusias hingga terlarut pada aktivitas pekerjaannya (Bakker & Leiter., 2010). Hal tersebut tercermin pada karyawan yang memiliki work engagement. Menurut Schaueli et. al. (2002), work engagement mengacu pada keadaan afektif motivasional yang positif dicirikan dengan adanya vigor, dedication, dan absorption. Work engagement akan terjadi ketika ada job demands dan job resources yang tinggi. Perceived organizational support merupakan salah satu job resources yang mencakup tiga dimensi yaitu fairness, supervisor support serta organizational rewards dan job condition. Tujuan dari penelitian ini adalah untuk melihat seberapa besar pengaruh perceived organizational support dan dimensinya terhadap work engagement pada 100 Barista Starbucks di Kota Bandung. Alat ukur yang dipergunakan dalam penelitian ini yaitu UWES-17 (Utrecht Work Engagement Scale-17) yang dikembangkan oleh Schaufeli et al. (2002). Selain itu, Survey Perceived organizational support (SPOS) oleh Eisenberger et. al. (1986) yang diadaptasi oleh Avianti & Hatta (2022). Hasil penelitian menunjukkan adanya pengaruh secara signifikan perceived organizational support terhadap work engagement sebesar 28.5% (R Square = .285). Dimensi organizational rewards dan job conditions berpengaruh signifikan dengan angka 20.8%. Sedangkan pengaruh terendah adalah dimensi fairness dengan angka 1.8%.